2021
DOI: 10.1101/2021.06.01.21257987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevention and Attenuation of COVID-19 by BNT162b2 and mRNA-1273 Vaccines

Abstract: BACKGROUND: Information is limited on messenger RNA (mRNA) BNT162b2 (Pfizer–BioNTech) and mRNA–1273 (Moderna) COVID–19 vaccine effectiveness (VE) in preventing SARS–CoV–2 infection or attenuating disease when administered in real–world conditions. METHODS: Prospective cohorts of 3,975 healthcare personnel, first responders, and other essential and frontline workers completed weekly SARS–CoV–2 testing during December 14 2020—April 10 2021. Self–collected mid–turbinate nasal swabs were tested by qualitative and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 25 publications
3
85
2
1
Order By: Relevance
“…18 We found that 85•3% of infections were asymptomatic, 92•5% among individuals younger than 19 years and 76•1% among individuals aged 19 years or older, despite active symptom evaluation twice a week. Three US-based cohort studies implementing PCR testing once a week for SARS-CoV-2, irrespective of symptoms, plus additional testing with symptomatic illness, found asymptomatic fractions of 31% in a community-based household cohort including children, 35% in pregnant women, and 11% among health-care workers, [19][20][21] which are lower than the estimates in our study. The lower asymptomatic proportion in these studies could be because swabbing twice a week allows identification of transient asymptomatic illness, or because the symptomatic fraction could be truly lower in the populations included in our study.…”
Section: Variantcontrasting
confidence: 91%
See 1 more Smart Citation
“…18 We found that 85•3% of infections were asymptomatic, 92•5% among individuals younger than 19 years and 76•1% among individuals aged 19 years or older, despite active symptom evaluation twice a week. Three US-based cohort studies implementing PCR testing once a week for SARS-CoV-2, irrespective of symptoms, plus additional testing with symptomatic illness, found asymptomatic fractions of 31% in a community-based household cohort including children, 35% in pregnant women, and 11% among health-care workers, [19][20][21] which are lower than the estimates in our study. The lower asymptomatic proportion in these studies could be because swabbing twice a week allows identification of transient asymptomatic illness, or because the symptomatic fraction could be truly lower in the populations included in our study.…”
Section: Variantcontrasting
confidence: 91%
“…The mean generation interval was 7•5 days (SD 4•8) (range 2-21 days after excluding outliers; appendix p 34). On multivariable analysis, generation interval was shorter if the index case was symptomatic, and longer if the index case shed virus for longer (>4 days vs ≤4 days) or was infected with alpha, beta or delta variant (vs wild-type; appendix pp [21][22].…”
Section: Sars-cov-2 Vaccine Statusmentioning
confidence: 99%
“…Inference was based on a partial likelihood approach. 24 Please recall that the effectiveness estimate for the Covid-19 vaccines in the Cox model with time-dependent vaccination status compares the risk of an event for children who received the vaccine and those who were unvaccinated at each event time. The risk group is determined by whether the child had received or not the vaccine shot in a speci c calendar time, and the comparison of the risk of an event is made at the same calendar time.…”
Section: Model Descriptionmentioning
confidence: 99%
“…See Online for appendix and real-world evidence show moderate to high vaccine efficacies in preventing virologically confirmed symptomatic disease, as well as reducing infectiousness or the probability of onward transmission. [12][13][14][15] Further real-world evidence shows that vaccination reduced 78% of PCRpositive infections among air passengers in Qatar. 16 Here, we account for the uncertainty in vaccine efficacy by considering σ m ∈(0•50, 0•60, 0•70, 0•80), which denotes efficacy in reducing susceptibility to infection; σ t ∈(0•30, 0•40, 0•50), which denotes efficacy in reducing infectiousness if infected; and σ s ∈(0•80, 0•90, 0•95), which denotes efficacy in reducing symptomatic diseases and admissions to hospital.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%